Progress in Clinical, Pharmacological, Chemical and Structural Biological Studies of Huperzine A: A Drug of Traditional Chinese Medicine Origin for the Treatment of Alzheimers Disease - JIANG, Hualiang; LUO, Xiaomin; BAI, Donglu (Current medicinal chemistry, 2003)
HupA is a potent, reversible AChEI, which crosses the blood-brain barrier smoothly, and shows high specificity for AChE with a prolonged biological half-life. It has been approved as the drug for the treatment of AD in China, and marketed in USA as a dietary supplement. HupA has been the subject of investigations by an ever-increasing number of researchers since 1980s. In the last four years, HupA has been further studied in many aspects such as the chemical synthesis, structural modification, structureactivity relationship, various biological effects, and mechanisms of action. A number of papers dealing with the computational modeling and X-ray crystallographic studies of HupA-AChE complex have also been published. This review represents a comprehensive documentation of the progress in the studies on HupA during the period of 1999-2002.